2003
DOI: 10.1126/science.1079469
|View full text |Cite
|
Sign up to set email alerts
|

Common Structure of Soluble Amyloid Oligomers Implies Common Mechanism of Pathogenesis

Abstract: Soluble oligomers are common to most amyloids and may represent the primary toxic species of amyloids, like the Abeta peptide in Alzheimer's disease (AD). Here we show that all of the soluble oligomers tested display a common conformation-dependent structure that is unique to soluble oligomers regardless of sequence. The in vitro toxicity of soluble oligomers is inhibited by oligomer-specific antibody. Soluble oligomers have a unique distribution in human AD brain that is distinct from fibrillar amyloid. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

166
3,880
11
31

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,776 publications
(4,140 citation statements)
references
References 17 publications
166
3,880
11
31
Order By: Relevance
“…Our dotblot, ThT staining and cytotoxicity assay results showed that scFv's could not only bind to ADDLs and Ab oligomers but also inhibit Ab fibrillation and cytotoxicity, which is consistent with previous report that binding to some oligomeric epitopes with specific antibodies may neutralize the toxicity of oligomers [9]. Selected scFv's can distinguish toxic Ab oligomers from monomers and fibrils, indicating that they may be used in the fields of diagnosis, the measurement of the oligomer species and the treatment for AD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our dotblot, ThT staining and cytotoxicity assay results showed that scFv's could not only bind to ADDLs and Ab oligomers but also inhibit Ab fibrillation and cytotoxicity, which is consistent with previous report that binding to some oligomeric epitopes with specific antibodies may neutralize the toxicity of oligomers [9]. Selected scFv's can distinguish toxic Ab oligomers from monomers and fibrils, indicating that they may be used in the fields of diagnosis, the measurement of the oligomer species and the treatment for AD.…”
Section: Discussionsupporting
confidence: 92%
“…Ab42 was purchased from American Peptide Company (Sunnyvale, CA, USA) and the Ab42 oligomers and fibrils were prepared as previously described with some modifications [9]. Briefly, Ab42 was dissolved in 100% 1,1,1,3,3,3-hexafluoro-2-propanal (HFIP) to a concentration of 1 mg/mL, sonicated in a water bath for 10 min, aliquoted into microcentrifuge tubes, dried under vacuum, and stored at À20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas monomeric forms are not toxic, these aggregates have been identified as toxic species responsible for the disease. Because a wide range of amyloidogenic proteins which do not share sequence homology at all, show similar biophysical characteristics after aggregation, it has been assumed that diverse amyloidoses may share a common mechanism of pathogenesis [2].…”
Section: Introductionmentioning
confidence: 99%
“…The principal neuropathological feature of this brain disease consists in polymorphous extracellular deposits called ''senile plaques''. The amyloid-beta peptide (Ab), the primary component of these plaques, was suggested to be the key factor in the development of AD pathology [2,3]. This peptide is produced by the proteolytic cleavage of the amyloid precursor protein by the b-and c-secretases to predominantly form 40-42 amino acid peptides [4].…”
Section: Introductionmentioning
confidence: 99%
“…The viewpoint that soluble oligomers act as cytotoxic species has garnered widespread attention since at least 1999 when it was noted that the abundance of soluble Aβ 1-42 oligomers is inversely correlated with neuronal degeneration in Alzheimer's disease whereas amyloid levels do not correlate [225,226]. In 2003, Glabe and co-workers discovered that soluble oligomeric species from several disease-related proteins shared a common structural epitope to which an antibody was developed [227]. Later studies showed that soluble oligomers are able to disrupt the polarity of cellular membranes [144,228,229], one possible basis for disease-associated toxicity.…”
Section: Protein Self-association and Aggregationmentioning
confidence: 99%